Potential of gambier leaf ethanol extract cream for incised wound healing - Arif, Maria Nisaul; Lumbantobing, Christina J. R. Esmaralda; Chiuman, Linda (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
Incised wounds are highly susceptible to bacterial infection, which requires stimulation of healing and restoration of normal function of the injured body part. This study aimed to test the effect of gambier leaf ethanol extract cream administration on the acceleration of wound healing on the skin surface of male Wistar rats. The research used a pre-test post-test with a control group design. Twenty male white rats were divided into four groups: control group (P0), treatment group 1 (P1), treatment 2 (P2), and treatment 3 (P3). The incision wounds in white rats were treated twice a day (in the morning and evening) for 14 days. Wound healing was observed by measuring the average length of the wound every day, from the first day of wounding until day 14. Statistical tests used were one-way ANOVA and post-hoc LSD test (p < 0.05). In this study, it was found that the 15% gambier leaf extract cream was more effective in wound healing in white rats than the 5% and 7.5% gambier leaf extract creams. However, in the group treated with 7.5% gambier leaf extract cream, the situation was already close to that in the treatment group treated with 15% gambier leaf extract cream. This is because, at a concentration of 7.5%, the secondary metabolite compounds in the gambier leaf extract had an effect on wounds, but at a concentration of 15% gambier leaf extract cream, the effect was similar to that of 15% gambier leaf extract cream.